1997
DOI: 10.1007/bf02912493
|View full text |Cite
|
Sign up to set email alerts
|

Human conversational behavior

Abstract: Observational studies of human conversations in relaxed social settings suggest that these consist predominantly of exchanges of social information (mostly concerning personal relationships and experiences). Most of these exchanges involve information about the speaker or third parties, and very few involve critical comments or the soliciting or giving of advice. Although a policing function may still be important (e.g., for controlling social cheats), it seems that this does not often involve overt criticism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
242
3
5

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 292 publications
(267 citation statements)
references
References 17 publications
10
242
3
5
Order By: Relevance
“…Most indirect reciprocity models, however, rely on individuals communicating information about the observed actions of others (21). Fortunately, we are more than happy to talk about how others have behaved: gossip is a central element of human communication (85,86). However, why did we come to have this predilection for gossiping about the previous behavior of others?…”
Section: Discussionmentioning
confidence: 99%
“…Most indirect reciprocity models, however, rely on individuals communicating information about the observed actions of others (21). Fortunately, we are more than happy to talk about how others have behaved: gossip is a central element of human communication (85,86). However, why did we come to have this predilection for gossiping about the previous behavior of others?…”
Section: Discussionmentioning
confidence: 99%
“…(woman, 67, higher education) "For everyone, even if you go to the market, something always happens to give you a reason to laugh, and when you meet other [women] you start to tell them, «hey, look at what soand-so did», or «listen to what someone said», and everyone starts to laugh and enjoy themselves, or there are also family problems, someone will say «listen to what my child said to me», it really is surprising how clever children are these days". (woman, 83, primary education) One other finding regarding gender differences is the degree to which women reported discussing topics related to family and children, topics which previous studies found to be very present in the conversations of women, but less so in those of men (Dunbar et al, 1997). Gender roles have arguably changed in recent times, allowing us to speculate that, for younger adults, the topics of conversation and humor production could no longer be clearly deliniated.…”
Section: Older Romanian Women and Experience-based Humormentioning
confidence: 82%
“…Studies that deal with the phenomenon of gossip suggest that it plays an important role in the social group, contributing to its functionality and to group cohesion by creating social bonding (Dunbar, 2004). One study found that only less than 3-4% of conversations classified as gossip were malicious, but that gossip in the form of exchange of social information can take up to 65% of dialogue time (Dunbar et al, 1997).…”
Section: Humor Production: Women Gossip and Men Bragmentioning
confidence: 99%
See 1 more Smart Citation
“…It is interesting to note that Dunbar marries the phylogentic argument about the role verbal grooming played in the emergence of language (in his view, verbal grooming substituted manual grooming as a more effective means of bonding in the growing hominid groups) with the statement on the nature of language which regards gossip, the contemporary manifestation of verbal grooming, as the essential characteristic of linguistic communication (see e.g. Dunbar et al 1997).…”
Section: T H E O R I a E T H I S To R I A S C I E N T I A R U M V Omentioning
confidence: 99%